Partial vertebrectomy with spine shortening for old spondyloptosis at the thoracolumbar spine: a case series study and literature review - Xu, Nuo; Liu, Ping; Kang, Yijun; Chen, Fei (Frontiers in Surgery, 2023)
Objective To report surgical outcomes of a serial cases and retrospectively analyze the value of partial vertebrectomy and spinal shortening in reduction of old spondyloptosis at thoracolumbar spine. Methods From 2015 to 2021, 8 patients who received spinal intervention of partial vertebrectomy and spinal shortening for thoracolumbar spondyloptosis over 3 weeks posttrauma were retrospectively summarized. Medical records and surgical outcomes were extracted for clinical safety and efficacy evaluation.Results Acceptable reduction and immediate stabilization were achieved for all 8 cases without causing iatrogenic damage to viscera. Mean operation time was 3.7 (Rang: 3.2-4.2) hours with blood loss average 1081 (Rang: 900-1300) ml.Postoperative stay days at spine department was average 11.4 (Rang: 8-17) days, followed by early rehab program. Mean VAS of low back pain decreased from preoperative 8.0 to 1.4 at the last follow-up. The average follow-up period was 19.9 months. As for neurological function recovery, 6 patients with preoperative ASIA A status remained unchanged throughout the follow-up period and improvement of one ASIA grade was indeed noted in 2 patients. At the latest follow-up, sound interbody fusion as well as good alignment of spine column was confirmed radiologically in 7 patients, while 1 patients encountered slight re-dislocation at 3 months after surgery, but eventually achieved spinal fusion.showed good efficacy and safety in managing old spondyloptosis of thoracolumbar spine, allowing for one-step good reduction and fusion for early rehabilitation.